5 - Pitfalls of Decentralization Reforms in Transitional Societies: The Case of Uganda - Muhumuza, William (Africa Development, 2021)
Decentralization reforms are in essence necessary if they have genuine demo- cratic objectives of empowering the people to make local-level governance effi- cient and effective. As the experience of Uganda reveals, donor-driven decen- tralization reforms have not performed according to expectations because of the converging external and domestic interests. This paper argues that for these reforms to succeed, the specific conditions pertaining to each country must be considered hand in hand with the honesty and political will of national leaders to genuinely transform power relations.